Difference in Subjective Accessibility of On Demand Recall of Visual, Taste, and Olfactory Memories - Zach, Petr (Biomed Res Int, 2018)
We present here significant difference in the evocation capability between sensory memories (visual, taste, and olfactory) throughout certain categories of the population. As object for this memory recall we selected French fries that are simple and generally known. From daily life we may intuitively feel that there is much better recall of the visual and auditory memory compared to the taste and olfactory ones. Our results in young (age 12–21 years) mostly females and some males show low capacity for smell and taste memory recall compared to far greater visual memory recall. This situation raises question whether we could train smell and taste memory recall so that it could become similar to visual or auditory ones. In our article we design technique of the volunteers training that could potentially lead to an increase in the capacity of their taste and olfactory memory recollection.